Designed structures for bone replacement - Yahamed, Azem; Ikonomov, Pavel; Fleming, Paul D.; Pekarovicova, Alexandra; Gustafson, Peter (Journal of Print and Media Technology Research, 2023)
Bone replacements are needed to help repair or replace damaged and diseased tissues ranging from trauma, degenerative disease, cancer and plastic surgery requirements. To create artificial bone implants from plastics, the structure and mechanical properties must be tested to closely match or be able to sustain greater forces than the original. It is essential to use proper bone replacement material that provides biocompatibility with sufficient stiffness and strength. The materials can be biocompatible polymers, such as polylactic acid (PLA), polyvinyl alcohol (PVA), polycaprolactone (PCL) and polyether-ether ketone (PEEK). Also, it is important to create internal structures that can accurately mimic the real human bone structure with a solid outer shell that represents the compact bone and porous internal volume that represents the trabecular (spongy) bone. Designing of the proper trabecular bone is one of the most critical steps, because its structure helps support the entire bone, while at the same time reduces the weight. Due to the low resolution of DICOM images, the trabecular bone structures cannot be obtained directly from CT and MRI scans. Therefore, we used CAD software – SolidWorks to design special 3D structures (hexagonal, triangular, and square). The reason for using these structures is that they are widely used in industry and aerospace applications, because they provide high strength, while keeping the weight low. The geometry of the void structure reduces the amount of material, reducing the overall weight and cost by reducing the structural density. We designed and produced 3D printed samples to test the structure properties with different geometric shapes. Structure property tests, such as tensile strength test, compressive strength test, and bending test were investigated. We found that the mechanical properties of the designed plastic structures either exceed or fall within the range of the mechanical properties of the human trabecular bones.